THE PROBLEM OF INFLAMMATION IN PERI-IMPLANT TISSUE AND FACTORS AFFECTING ITS COURSE - Safarov M.T; Tashpulatova K.M; Ruzimbetov H.B. (TADQIQOTLAR.UZ, 2023)
Annotation: Reducing the number of complications after dental implantation remains an urgent problem in dentistry. All risk factors can be divided into general - smoking, systemic pathology, condition after radiation therapy, etc., and local - poor oral hygiene, periodontal disease, iatrogenic conditions, design and quality of processing of the transgingival part of the implant. Understanding the course of inflammatory and destructive processes around a dental implant after its installation directs scientists and implant manufacturers to improve the already used conservative and surgical methods of treating these diseases, as well as greater attention to the prevention of this pathology, and, accordingly, the risk factors for its development. The development of new techniques for surgical interventions and prosthetics, the creation of new implant systems will help increase the service life of dentures on implants and improve the quality of life of patients.